The effects of information content of cash flow statement, dividend payout ratio, economic value added and corporate social responsibility on stock trading volume - Oktavianingsih, Dwi Luvira; Safkaur, Otniel; Sesa, Pascalina V. S. (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to empirically test and analyze the influence of information content of cash flow statements, Dividend Payout Ratio (DPR), Economic Value Added (EVA) Corporate Social Responsibility (CSR) on the trading volume of empirical study stocks in manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. Â Method - The number of samples used in this study was 169 taken from financial report on idx. The analytical techniques used were multiple regressions in order to obtain a comprehensive picture of the relationship between variable and each other. This research used a quantitative approach with its research population of companies included in the manufacturing sector listed on the Indonesia Stock Exchange in 2014- 2018..Result - Based on the results of this study, investment cash flow and Dividend Payout Ratio (DPR) significantly influenced the trading volume of stocks. Meanwhile, operating cash flow, funding cash flow, Economic Value Added (EVA) and Corporate Social Responsibility (CSR) had no significant effect on stock trading volume.Implication - This research is suggested to improve development of trading volume in investor decision making for investment and for companysâ€™ performance assessment.Originality - This research is the study that used content of cash flow resporting information, dividend payout ratio, economic value added, corporate social responsibility on stock trading volume.